The Effect of Organizational Culture on Knowledge Management and Managerial Performance of Government Department in Dubai - Saif, Mohamed Rashid; Nek Kamal Bin Yeop, (European Journal of Multidisciplinary Studies, 2020)
This study aim to emphasize the importance of knowledge management and the factors that influence the knowledge management within Dubai public sector organization. The study is to highlight the effect of organizational culture on the relationship between knowledge management and managerial performance of government departments in Dubai. Development of organizational culture is pegged on managerial performance. The role of the manager in any department is to evaluate the system and eliminate the impediments to success.As long as the mindset is built on competitive spirit, employees will be nurtured to appreciate superior performance amid their challenges. The manager should also act as a problem solver by understanding the existing challenges and using the available knowledge to create feasible solutions Data were collected by distributing questionnaires to 215 systematic randomly sampled respondents from seven public departments. Data collected were analyzed by using descriptive and inferential statistics. The research showed that the effect of organizational culture on knowledge management and managerial performance of government department in Dubai.
Keywords: Knowledge Management, Organization, Culture, Performance.